Circulating T helper 9 cells and increased serum interleukin‐9 levels in patients with knee osteoarthritis. (May 2016) - Qi, Changlin; Shan, Yuxing; Wang, Jing; Ding, Fupeng; Zhao, Ding; Yang, Teng; Jiang, Yanfang
Summary: The purpose of this study was to examine the roles of T helper 9 (Th9) cells and the serum interleukin (IL)‐9 level in the pathogenesis of osteoarthritis (OA). The numbers of IL‐9 +  CD4 +  CD8 − T cells, interferon (IFN)‐ γ + CD4 +  CD8 − T cells, IL‐4 + CD4 +  CD8 − T cells, and IL‐17A +  CD4 +  CD8 − T cells in 25 OA patients and 13 healthy controls (HC) were examined by flow cytometry. The serum concentrations of IL‐9, IL‐4, IL‐17A, and IFN‐ γ were also determined. The numbers of CD4 + CD45RO + T cells, Th9 cells, Th1 cells, and Th17 cells in OA patients were significantly higher than those in HCs. Furthermore, serum IL‐9, IL‐17A, and IFN‐ γ levels in OA patients were higher than those in HCs. The number of Th9 cells was positively correlated with the number of Th17 cells in OA patients. Furthermore, greater numbers of Th9 cells were positively associated with elevated C‐reactive protein, and both Th9 cells and IL‐9 levels were positively correlated with the Western Ontario and McMaster Universities Osteoarthritis index in OA patients. Th9 cell numbers and IL‐9 levels are correlated with OA patient symptoms and joint functionality and may be a marker of disease activity.